2022
DOI: 10.1007/s11357-022-00530-6
|View full text |Cite
|
Sign up to set email alerts
|

Examination of pituitary adenylate cyclase-activating polypeptide in Parkinson’s disease focusing on correlations with motor symptoms

Abstract: The neuroprotective effects of pituitary adenylate cyclase-activating polypeptide (PACAP) have been shown in numerous in vitro and in vivo models of Parkinson’s disease (PD) supporting the theory that PACAP could have an important role in the pathomechanism of the disorder affecting mostly older patients. Earlier studies found changes in PACAP levels in neurological disorders; therefore, the aim of our study was to examine PACAP in plasma samples of PD patients. Peptide levels were measured with ELISA and corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 101 publications
0
6
0
1
Order By: Relevance
“…Although the significant correlation between PACAP levels and age has not been described in either healthy or patient populations, recently, our research group demonstrated significantly lower PACAP levels in a population of Parkinson’s disease patients older than 50 years. In this case, however, an increase in younger patients due to deep brain stimulation could not be excluded [ 17 , 20 ]. Thus, our study is currently the first in clinical research to demonstrate a significant decrease in the plasma PACAP levels in correlation with the age of the MM patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the significant correlation between PACAP levels and age has not been described in either healthy or patient populations, recently, our research group demonstrated significantly lower PACAP levels in a population of Parkinson’s disease patients older than 50 years. In this case, however, an increase in younger patients due to deep brain stimulation could not be excluded [ 17 , 20 ]. Thus, our study is currently the first in clinical research to demonstrate a significant decrease in the plasma PACAP levels in correlation with the age of the MM patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, significant alterations of this peptide have been detected in human tissues under various physiological and pathological conditions (e.g., neurological disorders: Parkinson’s disease, posttraumatic stress disorder; cardiac disorders: cardiomyopathies, acute myocardial infarction; kidney disorders: nephrotic syndrome, nephrectomy), in addition to various malignant disorders. These results suggest a potential role of PACAP in the diagnosis, prognosis, and clinical therapy of certain diseases [ 11 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Significant elevation of PACAP levels was observed in the most severe stage of Epworth sleepiness scale, measuring the severity of sleep disturbances. In PD patients older than 50 years at the time of diagnosis significantly lower PACAP levels were found compared to those who were younger, although patients without DBS treatment were older compared to DBS–treated patients ( 34 ). Interestingly, a similar age–related finding, as a transition decade, was described in case of human choroid plexus (CP) aging, which confirmed the results of previous in vivo experiments in which altered CP transcriptome was detectable in various central nervous system disorders ( 35 ).…”
Section: Neurological and Psychiatric Diseasesmentioning
confidence: 99%
“…The brain-gut peptides related to the pathogenesis and treatment of PD mainly include GLP-1, ghrelin, nesfatin-1, and pituitary adenylate cyclase-activating polypeptide (PACAP) ( Dong et al, 2019 ). Serum levels of them show varying degrees of reduction in PD patients ( Song et al, 2017 ; Emir et al, 2019 ; Pham et al, 2022 ).…”
Section: Gut-brain Axis Pathogenesismentioning
confidence: 99%